The effect of methanol and water plant extracts of Cordia myxa on Some pathogenitic bacteria and Candida albicans - Baghdad Science Journal (مجلة بغداد للعلوم)
this study aimed to study the effect of Cordia myxa extract on the growth and activities of the following types of bacteria : Escherichia coli , Pseudomonas aeruginosa, Proteus Spp., Klebsiella pneumoniae , Staphylococcus aureus, Streptococcus pyogenes , Bacillus subtilus, and the yeast Candida albicans .the results showed an inhibitory effect of the methanol extract on both the growth and activity of the tested microbes .this was reflected by the minimum inhibitory concentration ( MIC ) of different type of bacteria and the yeast.